The journey to sustainable universities: Insights from a Brazilian experience - De Deus, Rafael Mattos [UNESP]; De Castro, Rosani [UNESP]; Vieira, Karina Rabelo Ogasawara [UNESP]; Leite, Antônio Edson [UNESP]; Jabbour, Charbel José Chiappetta [UNESP] (Inderscience Publishers, 2015)
Universities play a key role in humanity's search for sustainable development. This paper presents the results of preliminary studies on projects regarding campus sustainability, conducted at Universidade Estadual Paulista 'Julio de Mesquita Filho' - UNESP's Bauru Campus, State of São Paulo. It recommends the constitution of a sustainability committee, with a public participation and social responsibility (PPSR) framework, and the implementation of a campus sustainability program. The study also describes how social responsibility and sustainability can bring UNESP/Bauru economic advantages.
Keywords: Business social responsibility; Environment and development; Higher education institutions; Sustainability; University